Quo vadis Patria Gaucha? Uruguayan pathways of land use change - Säumel, Ina; Alvarez, Jorge; Ramírez, Leonardo R.; Barra, Marcos (Frontiers in Sustainable Food Systems, 2023)
South American grasslands are heavily used socio-ecological systems since long and currently experience dramatic land-use changes by the implementation of large-scale afforestation and agro-industrial cash crops for the global market. We applied the conceptual framework of ‘Multifunctional and sustainable productive landscapes’ to Uruguay and explored the impacts of land-use change on rural ecosystems and communities based on a long-term monitoring network assessing species richness of plant and terrestrial arthropod and including socio-economic data from national census. Silvi- and agricultural industry established at the expense of extensively grazed grasslands, of local family farms with traditional techniques and along with a deregulation of rural labour market, depopulation and aging of rural society. Governmental nature protection efforts gain an increase of native forest cover and establish nature protection areas, mainly focused on forests. We discuss pathways of land-use change within the last decades and related discourses of local stakeholders.